'In me porto crucem': a new light on the lost St Margaret's crux nigra. (December 2018) - Marzella, Francesco
Abstract: St Margaret of Scotland owned a reliquary containing a relic of the True Cross known as crux nigra . Both Turgot, Margaret's biographer, and Aelred of Rievaulx, who spent some years at the court of Margaret's son, King David, mention the reliquary without offering sufficient information on its origin. The Black Rood was probably lost or destroyed in the sixteenth century. Some lines written on the margins of a twelfth-century manuscript containing Aelred's Genealogia regum Anglorum can now shed a new light on this sacred object. The mysterious lines, originally written on the Black Rood or more probably on the casket in which it was contained, claim that the relic once belonged to an Anglo-Saxon king, and at the same time they seem to convey a significant political message.